Representations of Teachers about Their Own Work in Inclusive Practice - T.Y. Sunko (Moscow State University of Psychology and Education, 2020)
The work of teachers in inclusive education inextricably linked with the assuming of the values of inclusion concept, adaptation and individualization of the education process. The aim of the pilot study conducted in 2018 was the determination of the representations of teachers about the inclusive practice and the characteristics of their work activities. Educational workers of Moscow schools aged 30 to 50 years (N = 16) with higher education and experience in inclusive practice for more than three years participated in the study. Data was obtained with the use of questionnaire; conventional content analysis used to process the results. The results demonstrate that the specificity of teachers, who implements an activity-based and differentiated approaches, position on the necessity of conditions for learning in an inclusive school is the following: making of host environment (24 %), educational content adaptation (26 %), individualization of tasks (30 %).